Co-carriage of respiratory tract bacterial pathogens among under-5 children with pneumococcal carriage in Peninsular Malaysia - Tan, Andrew Chun Hoong; Ramzi, Nurul Hanis; Johari, Nur Alia; Lai, Pei Kuan; Wong, Simone; Chang, Xuan Qi; Lin, Eileen Eng Jia; Lum, Xin Ru; Md Roslan, Azim Haikal; Nathan, Anna Marie; Teh, Cindy Shuan Ju; Ilias, Mohamad Ikram; et al. (BioMed Central Ltd., 2026)
Background Streptococcus pneumoniae (SPN) is the commonest cause of bacterial childhood pneumonia, and adverse clinical outcomes have been associated with co-infections with other bacteria causing severe respiratory disease. We therefore conducted a study to look for evidence of other respiratory bacterial pathogens and to determine the prevalence and risk factors of co-carriage status among under-5 children in Peninsular Malaysia.